The Cytogenetic Landscape of Pediatric Chronic Myeloid Leukemia Diagnosed in Chronic Phase - Karow, Axel; Göhring, Gudrun; Sembill, Stephanie; Lutterloh, Friederike; Neuhaus, Fina; Callies, Sara; Schirmer, Elke; Wotschofsky, Zofia; Roche-Lancaster, Oisin; Suttorp, Meinolf; Krumbholz, Manuela; Metzler, Markus (Cancers, 2022)
Philadelphia chromosome-positive chronic myeloid leukemia (CML) is cytogenetically characterized by the classic translocation t(9;22)(q34;q11), whereas additional non-Philadelphia aberrations (nPhAs) have been studied extensively in adult patients with CML, knowledge on nPhAs in pediatric patients with CML is still sparse. Here, we have determined nPhAs in a cohort of 161 patients younger than 18 years diagnosed with chronic phase CML and consecutively enrolled in the German national CML-PAED-II registry. In 150 cases (93%), an informative cytogenetic analysis had been performed at diagnosis. In total, 21 individuals (13%) showed nPhAs. Of these, 12 (8%) had a variant translocation, 4 (3%) additional chromosomal aberrations (ACAs) and 5 (3%) harbored a complex karyotype. Chromosome 15 was recurrently involved in variant translocations. No significant impact of the cytogenetic subgroup on the time point of cytogenetic response was observed. Patients with a complex karyotype showed an inferior molecular response compared to patients carrying the classic translocation t(9;22)(q34;q11), variant translocations or ACAs. No significant differences in the probability of progression-free survival and overall survival was found between patients with nPhAs and patients with the classic Philadelphia translocation only. Our results highlight the distinct biology of pediatric CML and underline the need for joint international efforts to acquire more data on the disease pathogenesis in this age group.
CRIS-Team Scopus Importer:2022-04-08
Keywords: additional chromosomal aberrations; chronic myeloid leukemia; complex karyotype; cytogenetic response; molecular response; pediatric chronic myeloid leukemia; Philadelphia chromo-some; tyrosine kinase inhibitor treatment; variant translocations